Efficacy and safety of imeglimin add‐on to insulin monotherapy in Japanese patients with type 2 diabetes (TIMES 3): A randomized, double‐blind, placebo‐controlled phase 3 trial with a 36‐week open‐label extension period. Issue 5 (8th February 2022) - Reilhac, Caroline; Dubourg, Julie; Thang, Carole; Grouin, Jean‐Marie; Fouqueray, Pascale; Watada, Hirotaka
Abstract: Aims: To evaluate the efficacy and safety of imeglimin for up to 52 weeks as combination therapy with insulin in Japanese patients with type 2 diabetes. Materials and Methods: This double‐blind, randomized, parallel‐group phase 3 trial was performed at 35 sites in Japan. Eligible patients were individuals aged ≥20 years with type 2 diabetes and inadequate glycaemic control with insulin. Patients were randomly assigned (1:1) to either imeglimin (1000 mg twice daily) or matched placebo, in combination with insulin, for 16 weeks. In a subsequent 36‐week, open‐label extension period, all patients received imeglimin 1000 mg twice daily. The primary endpoint was change in mean glycated haemoglobin (HbA1c) from baseline to week 16. Results: In all, 108 and 107 patients were randomly assigned to treatment with imeglimin 1000 mg twice daily or placebo, respectively. Compared with placebo, the adjusted mean difference in change from baseline HbA1c at Week 16 was −0.60% (95% confidence interval [CI] −0.80 to −0.40; P  < 0.0001). This decrease was sustained up to 52 weeks with a mean decrease of −0.64% (95% CI −0.82 to −0.46) versus baseline. The incidence of patients experiencing adverse events and serious adverse events was similar in the two treatment groups. The number of patients experiencing hypoglycaemia was similar in the two treatment groups. In patients receiving imeglimin, all hypoglycaemic events were mild in severity; no episodes required assistance. Conclusions: Imeglimin significantly improved HbA1c in Japanese patients with insufficiently controlled type 2 diabetes by insulin and had a similar safety profile to placebo. The efficacy of imeglimin on top of insulin was sustained for 52 weeks. Imeglimin represents a potential new treatment option for this population as add‐on to insulin therapy.